Imperial Horizons of the Silk Roads Archaeological Case Studies. - Franicevic, Branka (Archaeopress, 2023)
This volume centres on how the exchange routes transformed the frontier regions of the Silk Road. In doing so, it utilises a range of methods to reach an archaeological interpretation of the factors that linked people with the environment; movements, settlements, and beliefs.